Assessing the genetic diversity of finger millet (Eleusine coracana) germplasm for agronomic traits - SINGH, ANOOP; SEHRAWAT, KRISHAN D; SEHRAWAT, ANISH; SINGH, MANJEET; RANI SEHRAWAT, ANITA (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during the rainy (kharif) season of 2019 and 2020 at research farm of CCS Haryana Agricultural University Hisar, Haryana to assess the genetic diversity of finger millet [Eleusine coracana (L.) Gaertn.] germplasm for agronomic traits. Experiment consisted of 150 accessions and 4 checks in augmented block design. The analysis of variance (ANOVA) divulged that test genotypes showed a highly significant difference (P